Interpretation of Temperature Performances at U-Tube Ground Heat Exchangers in Heterogeneous Formations - FUJII Hikari; OKUBO Hiroaki; ITOI Ryuichi; KOSUKEGAWA Hiroyuki (Journal of the Geothermal Research Society of Japan, 2006)
The performances of U-tube ground heat exchangers (GHEs) in heterogeneous formations were predicted using a newly developed analytical modeling approach based on the cylindrical source function. The modeling procedure transforms the detailed vertical temperature profiles obtained with fiber optical temperature sensors to thermophysical properties of ground. The vertical distribution of thermal conductivities and heat exchange rates were estimated using a non-linear regression method. The estimated distribution of thermal conductivity correlated well with the geological and groundwater flow conditions at the well location, while the distribution agreed well with the interpretation results in an adjacent GHE completed with a co-axial heat exchanger.